Ambivalent Sexisms Role in Determining Responsibility for Gender Differentiated Negative Events - Vapsva, Juliet (My University, 2018)
I am interested in discovering if women take harsher blame for negative events that happen while under the influence of alcohol. This idea came to me because of one particular incident that I witnessed at a university. I noticed two college students, one male and one female, making a mistake while drinking. The female college student received harsh blame from friends and other students while the male college student did not. Instances like this can be seen in many different scenarios, especially with college aged students where these alcohol related situations or mistakes may be more prevalent. College age students are, for the majority, drinking alcohol for the first time. For most college students, they cannot drink legally until their second or third year in college but even before they can legally drink, they have access to excess amounts of alcohol with little to no supervision. They interact with it more often and on a larger scale than many other ages that I could have measured which is why they were the best possible group to use in this experiment. College students are more likely than other groups to drink heavily, binge drink, and have alcohol dependence. Making poor decisions under the influence of alcohol is something that can and does happen to both genders. I realized that an experiment with college students would best allow me to explore gender differences when it comes to responsibility for these types of events. I decided to do a study to see if an individual's Hostile and Benevolent Sexism inventory is something that can lead participants to place more blame on bad decisions made by females than by males. I studied this potential bias using two different quantitative methods which will be discussed at greater lengths under the methodology section. The purpose of this study was to determine if gender bias is a factor that would affect an individual's rating of responsibility for negative events when alcohol is involved.
Keywords: Alcohol; Sexism; Social perception